Effect of staggered V-shaped and rectangular grooves copper surfaces on pool boiling heat transfer enhancement using ZrO2 nanofluids - Gajghate, Sameer Sheshrao (2021)
Boiling heat transfer has been a trending research area for the last several decades due to its excellent heat removal capacity and direct applications in the distillation and pharmaceutical industries. The present investigation focuses on the augmentation of efficiency for the boiling requiring applications, as highlighted earlier. The experimental and numerical investigations study the effect of staggered V-shaped and rectangular grooved copper surfaces on pool boiling, compared with the smooth copper surface in the ZrO2 nanofluid media. The authors adopted fiber laser engraving technology to form the highlighted microstructures. Furthermore, three different concentrations, i.e., 0.001%, 0.005% and 0.01% by volume, were investigated in a medium having equal volumes of distilled water and ethylene glycol. The thermophysical properties of nanofluid and peculiar microstructures enhanced the relative heat transfer coefficient by 41.48%. The wall superheat drastically reduced due to the micro-level convection on the boiling heat transfer promoted by the microstructures. Besides, the numerical results fitted well with the experimental results with a little deviation (MAE = 2.04%).